A comparative study on sample size requirements based on the methods of probits and logits. - Jardeleza, Ma. Theresa R.
An investigation in the area of sample size is pursued in this study and a comparative analysis between 2 methods, Probits and logits is likewise undertaken. Practical application of the formulas derived for sample size is used on data age at Menarche. The study design follows the dosequantal response scheme.
Thesis (MS Public Health, Biometry)--University of the Philippines Manila, 1979
Keywords: Transformations (Mathematics); Probits and logits; Biological assays